AN ANALYSIS OF READING COMPREHENSION QUESTIONS IN THE “BAHASA INGGRIS WORK IN PROGRESS” TEXTBOOK FOR TENTH GRADE STUDENTS - Astari, Melya Putri; Sutrisno, Djoko (IKIP Siliwangi, 2024)
Reading comprehension is crucial in language learning as it improves vocabulary, grammar, and general language proficiency. However, a report points out that Indonesian students' English proficiency remains lacking, partly because the proportion of Higher-order Thinking Skills (HOTS) distribution in textbooks is low. This study attempts to analyze the dominant categories of cognitive process dimensions and examines the proportion of cognitive process dimensions between Lower-order Thinking Skills (LOTS) and Higher-order Thinking Skills (HOTS) in the textbook “BAHASA INGGRIS Work in Progress” for grade 10 senior high school. Utilizing a descriptive quantitative method and Revised Bloom’s Taxonomy, 67 questions from 6 chapters in the textbook were explored. The results show that 59.7% of the reading questions focused on HOTS, with the Analyzing being dominant at 45.58%, Understanding at 22.05%, Evaluating at 17.65%, Remembering at 10.29%, and Creating at 4.48%, with no representation in the Applying. The study concludes that the textbook effectively integrates HOTS, aligning with the educational principle and addressing the need for balanced cognitive skill development in Indonesian senior high schools, primarily in English education. Future research could explore how teachers utilize and improve these materials to enhance HOTS in classroom settings by involving classroom observations and interviews.